REMEDIATION OF CONTAMINATED SOIL WITH CRUDE OIL BY COMPOSTING - Yap, Chi Nam; Hadibarata, Tony (Journal of Civil Engineering, Science and Technology, 2022)
In recent years, one of the primary issues noted worldwide in the environment is the contamination of crude oil in soil. In comparison to traditional methods, bioremediation offers a potential alternative for removing hydrocarbon pollution from the environment. This review paper gives an overview of the benefits, mechanism, and operation of aerobic composting remediation of soil contaminated with crude oil. Within this study, it was demonstrated that with composting technology, one could successfully treat crude oil contaminated soil with a > 90% removal efficiency. Aerobic composting utilizes aerobic bacteria and fungi that require oxygen to grow and biodegrade crude oil’s biological component into carbon dioxide and water, whereas anaerobic composting utilizes anaerobic microbes that grow in the absence of oxygen and convert the crude oil’s organic component primarily into methane. In terms of efficiency, biodegradation capacity, and rate, aerobic conditions outperform anaerobic conditions. Numerous parameters have been discussed and demonstrated to have an effect on the composting condition and also on the bacteria and fungi used to biodegrade crude oil contaminants at various stages of the composting process, including initial concentration, soil type, soil/compost ratio, aeration rate, moisture content, C/N ratio, pH, and temperature. Microbes use crude oil organic matter as carbon and energy sources during the composting process, whereas fungi produce enzymes that catalyze crude oil oxidation reactions. It is believed that the mutualistic and competitive interactions between bacteria and fungi maintain a robust biodegradation system. The thermophilic phase exhibited the highest rate of biodegradation. However, the presence of a diverse and dynamic microbial community throughout the composting process ensures that crude oil degradation occurs. The efficient composting processes using specific microbes need to be investigated.